Connectivity of a Gaussian network. (21st May 2008) - Balister, P.; Bollobas, B.; Sarkar, A.; Walters, M.
Following Etherington, Hoge and Parkes, we consider a network consisting of (approximately) N transceivers in the plane R² distributed randomly with density given by a Gaussian distribution about the origin, and assume each transceiver can communicate with all other transceivers within distance s. We give bounds for the distance from the origin to the furthest transceiver connected to the origin, and that of the closest transceiver that is not connected to the origin.